Social interactions and female voting in rural Paraguay: The role of urbanization patterns on the effectiveness of GOVT campaigns - Alberto Chong; Gianmarco León; Vivian Roza; J. Martín Valdivia; Gabriela Vega (Inter-American Development Bank (IDB), 2018)
We use a field experiment to evaluate the impact of two informational get-out-the-vote (GOTV) campaigns to boost female electoral participation in Paraguay. We find that public campaigns had no effect either on the probability of registration, or on voter turnout in the 2013 presidential election. However, households that received door-to-door (D2D) treatment were four percentage points more likely to vote. Experimental variation on the intensity of the treatment at the village level allows us to estimate spillover effects, which are present in localities that are geographically more concentrated, and thus may favor social interactions. The effect of reinforcement of the message to the already treated population is twice as large as the diffusion to the untreated. Our results underscore the importance of taking into account urbanization patterns when designing informational campaigns.
Keywords: O10; D72; O53; D71; 330; Voter Behavior; Electoral Politics; Urbanization; Spillover Effects; Paraguay